Establishing Surgical Care Sustainability in Sub-Saharan Africa for Global Child Health: Insights From Pediatric Cardiac Surgical Capacity-Building Programs in Ethiopia and Côte d'Ivoire - Park, Jayoung; Heo, Jongho; Kim, Woong-Han (Frontiers in Pediatrics, 2022)
The global surgery research team of the JW LEE Center for Global Medicine, Seoul National University College of Medicine, introduced team-based health workforce training programs for pediatric cardiac surgery in Ethiopia and Côte d'Ivoire. A team-based collaborative capacity-building model was implemented in both countries, and details of the program design and delivery were documented. The research team shared their experiences and identified achievements, lessons, and challenges for cardiac surgical interventions in Sub-Saharan Africa. Future directions were put forward to advance and strengthen the low-and middle-income countries “Safe Surgery.”